The Subject Is Still There. Judicial Statements and Mexican Political-Military Organizations in the Seventies - Aguirre, Aleida García (Journal of Latin American cultural studies : travesía, 2022)
This article analyses the judicial statements of members of political-military organizations that were obtained by agents of the national security and intelligence institution Dirección Federal de Seguridad (Federal Security Department; DFS) during the seventies. The analysis proposes that the conditions in which these documents were produced, as well as their dialogic and uneven nature, brought about narratives of the lives of the detainees that may be used as an index to understand certain aspects of these militants' process of subjectivation. For example, the heterogeneity of their social origins and the diverse spaces about which they spoke, as a way to account for their political trajectory prior to their participation in armed militancy, and how they conceptualised both the organisation and their militancy. At the same time, it is also possible to find certain traces about the DFS agents who interrogated them: their bias against the militants, the aspects and features of the lives of the detainees that were inaudible to them. The corpus of DFS statements, as a discourse, provides a useful resource for problematising our conception of who the militants and agents of repression were, and for broadening the history of Mexico's recent past.